Prevalence of stress and the stressor during the covid-19 endemic era among healthcare students at International Islamic University Malaysia (IIUM) - Hassan, Nor Athirah; Ruslan, Rusila (IIUM Press, 2023)
Introduction: The COVID-19 pandemic has introduced challenges across diverse facets of human life, profoundly affecting the mental health of individuals, including students, regardless of their fields. This study delves into the intricate relationship between socio-demographic factors and stress among undergraduate healthcare students at IIUM during the endemic phase of COVID-19. Factors such as gender, race, academic year, kulliyyah, study support, family financial status, and psychological history are examined in connection to stress incidence. The motivation for this investigation stems from the limited and scattered data available for this specific pandemic phase. Method: Employing a cross-sectional design, the study utilized random stratified sampling, focusing exclusively on active undergraduate healthcare students who underwent clinical postings during the pandemic. The analysis included students from the Kulliyyah of Medicine, Nursing, Dentistry, Pharmacy, and Allied Health Sciences. Data collection involved an online Google Form questionnaire encompassing the PSS-10, Undergraduate Source of Stress questionnaire, and an open-ended question. Results: Within the study participants, 26 individuals (14.7%) indicated experiencing low stress levels, while 126 students (71.2%) reported moderate stress, and 25 students (14.1%) expressed high perceived stress. Analyzing the distribution of stress among healthcare students at IIUM, it was observed that KON students had the highest proportion at 49.2%, followed by KAHS at 18.1%, KOM and KOD both at 11.3%, and KOP at 10.2%. SPSS version 27.0 facilitated data analysis, revealing no significant association between socio-demographic factors and stress levels. Contributing factors to stress included course material volume, time demands, uncertainty about course expectations, intellectual demands, and university fees. Conclusion: Despite the challenges, most healthcare students exhibited controlled, moderate stress levels during the transition from pandemic to endemic phases.